Diagnosis of Testicular Torsion and Differentiation From Other Pathologies Using Near-Infrared Spectroscopy - ŞEKERCİ, ÇAĞRI AKIN; YÜCEL, SELÇUK; ÇAM, HAYDAR KAMİL (My University, 2023)
© 2023 Elsevier Inc.Objective: To develop a near-infrared (NIR) spectroscopy device to diagnose testicular torsion with high sensitivity and specificity. Specifically, we aim to investigate the differentiation between testicular torsion from other pathologies such as orchidoepididymitis, varicocele, and hydrocele. Methods: Two LEDs with wavelengths of 660 nm and 940 nm were used as light sources in the device. Each wavelength was sent to the testicle successively, and a photodiode detected back-reflected diffuse light. The ratio of the light intensities of 660 nm and 940 nm was used as a diagnostic parameter. A multi-center clinical trial was performed in 5 different hospitals. Results: In total, 62 patients in urology clinics with acute testicular pain have been recruited for the study. The developed NIR spectroscopy correctly defined all 8 testicular torsion cases. Besides, 3 orchidoepididymitis, 1 varicocele, and 3 hydrocele cases were correctly distinguished from testicular torsion. Only 1 hydrocele case was misdiagnosed as torsion. The range of the ratio was between 0.14 and 1.16 overall measurements. The ratio varied between 0.14 and 0.3 for the testicle with torsion. The ratio was between 0.49 and 1.16 for the normal testicle and testicle with other pathologies mentioned above. Conclusion: We have chosen the threshold ratio of 0.4 to differentiate between the normal and torsion testis and diagnosed all the torsion cases among all normal and other pathologies. The developed optical device to diagnose testicular torsion is inexpensive, user-friendly, and works based on objective criteria with high sensitivity and specificity in real time.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; Üroloji; Urology